An Augmented Reality System for Biology Science Education in Malaysia - Ng, Giap Weng; Oon, Y.B.; Lee, Hong Yew; Teoh, Ee Hsia (UTM, 2016)
This paper presents an educational application for Form 4 Biology Science in Malaysian secondary schools using Augmented Reality (AR) technology, includes topics of mitosis, meiosis, respiration and their systematic relations. Worth mention is knowledge is a whole in which no part is really isolated but more or less systematically related to others. Knowing regularities is essential for having a concept at students’ disposal as well as for object perception. An implicit understanding of regularities is a precondition of object perception. Having a concept means being able to assert that something, such as a specific attribute, a rule or a function, applies to all the objects of the same kind. These lessons are presented in dedicated stereoscopic and photo-realistic views, thus facilitating students in noticing, memorizing and understanding Biology concepts. Also, it allows students individualized interaction while enabling social communication, given thinking is but epistemic in its nature and that its organization has both individual and social dimensions. AR technology introduces a new type of automated applications and to enhance the effectiveness and attractiveness of learning environment for the students in a real world scenario. This AR study emphasizes on merging computer vision, image processing and computer graphics to form a new Human-Computer Interaction (HCI) paradigm.